Statistical modeling of low-temperature properties and FTIR spectra of crumb rubber modified asphalts considering SARA fractions. (10th November 2022) - Wang, Tao; Weng, Yuxin; Cai, Xiaopei; Li, Jin; Xiao, Feipeng; Sun, Guoqiang; Zhang, Fan
Abstract: In this study, the correlation between low-temperature performance of the crumb rubber modified asphalt (CRMA) binders and their chemical fractions was investigated. The low-temperature properties of CRMA binders were firstly characterized by creep stiffness and creep rate using the bending beam rheometer (BBR) test. Secondly, the SARA fractions, namely saturates, aromatics, resins, and asphaltenes, were separated from CRMA binders using an improved column chromatography method. Meanwhile, the functional groups and the derived indexes of CRMA binders and SARA fractions were characterized using Fourier transform infrared (FTIR) spectra, respectively. Finally, statistical modeling was conducted between low-temperature properties and functional groups of CRMA binders and their SARA fractions. The results showed SARA fractions from CRMA binders contained substances released from the partially degraded crumb rubber modifiers, indicated by the emergence of peaks at 1100 cm −1, 967 cm −1, and other wavenumbers in FTIR spectra. The substance exchanges played a positive role in improving the low-temperature performance of CRMA binders. Meanwhile, the addition of crumb rubber could effectively inhibit the increase of polar functional groups in the aging process, such as carbonyl of aromatics, resins, and asphaltenes fractions. This thus significantly resisted the aging and improved the low-temperature performance of CRMA binders. Finally, the statistical modeling showed the stiffness modulus and creep rate of CRMA binders were highly correlated with functional groups of aromatics, resins and asphaltenes. This indicated that SARA fractions significantly affected the low-temperature properties of CRMA binders. Graphical abstract: Image 1 Highlights: SARA fractions were separated from CRMA binders using an improved column chromatography method. FTIR spectra of base and CRMA binders as well as SARA fractions were compared. Statistical modeling was conducted between the low-temperature properties of CRMA binders and functional groups of their SARA fractions.